Konflik Hukum Dalam Tradisi Sifon Suku Atoni Pah MetoDi Provinsi Nusa Tenggara Timur (Studi Tentang Konflik Dan Resolusi Konflik Dalam Sistem Hukum Indonesia) - Hidayat, Nur Azizah; , Prof. Dr. Harun; , Dr. Nurhadiantomo (2017)
Sifon's Tradition is the tradition of circumcision to men over the age of 17 years old and they had sexual intercourse. The uniqueness of ritual circumcision of Atoni Pah Meto's tribe in East Nusa Tenggara province is on the healing process of wounds from circumcision, that is by having sexual relations with a woman who not his wife or a close family member, or a woman who will not be married to a man who have Sifon's ritual. The Sifon's Tradition have a potential conflict, either between women , indigenous peoples of Atoni Pah Meto, nor the State Law. This research aimed to know the position of the Sifon's Tradition in the Legal System of Indonesian Positive Law, analized conflict and other forms of conflict resolution caused by Sifon's Tradition, with disputed positions of Sifon's Tradition in the Legal System of Indonesian Positive Law; potential conflicts and forms of conflict resolution caused by Sifon's Tradition, viewed from the perspective of Feminism and Positivism. This research is a Feminist Law in socio-legal perspective, using legal methods doctrinal and non-doctrinal legal methods. The research proves that Sifon's Tradition is the Tribal Law of Atoni Pah Meto, which legitimized the structural oppression women of Atoni Pah Meto's tribe. Sifon's Tradition also violated the State Law, which deals with offenses morality, adultery, trafficking of women, and human rights. One resolution of the conflict is by using of Responsive Law.